HINDI MOVIES: AN OVERVIEW OF PSYCHIATRY - Narula, Bani (International Journal of Psychosocial Rehabilitation, 2020)
The ensuing paper addresses an emerging trend witnessed in the present day movies and cinema i.e. how movies related to psychological principles impact our society? To attend this question, the researcher’s replies with an overview of Indian Hindi movies and it can be asserted that it continues to have a great impact on the psyche of the masses, thus may serve as a promising area of study in human psychology. A good movie is regarded higher than any education and it fosters a greater understanding to broaden awareness, correct measures and wakefulness of issues as drug addiction, alcohol and substance dependence and clinical disorders. The researcher in this paper which is a qualitative research aims to explore popular Hindi movies that thematically explore certain prevalent psychological disorders. Those movies are chosen that are made between 2005 and 2019 and review focusing on psychiatric issues and understand its effect on the layman’s perceptions of them